Shrinking shrimps - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The volume of industrial fishing of shrimps off Madagascar is lower than expected. The targeted level was 8,000 tonnes, but the current harvest has yielded less than 7,000 tonnes compared with the exceptional levels of 9,250 in 1998. The cause does...